Acaricidal Effect of Zeolite and Kaolin Against Tyrophagus putrescentiae on Wheat - Christos G. Athanassiou; Christos I. Rumbos; Paraskevi Agrafioti; Maria K. Sakka (Agronomy)
Different inert materials have been tested as grain protectants against stored-product mites with variable results. Most of the studies are focused on the efficacy of diatomaceous earth, but there are few comparable data on other types of inert dust. In this study, we have tested two inert materials, zeolite and kaolin, against the cheese mite Tyrophagus putrescentiae (Schrank) (Astigmata: Acaridae) on wheat. Mites were reared in the laboratory under controlled conditions of 25 °C and 80% relative humidity. Bioassays were conducted to assess the acaricidal effects of zeolite and kaolin. These formulations were applied to wheat kernels at 100, 500, and 1000 ppm. The treated wheat was manually mixed and divided into 1 g subsamples, each containing ten T. putrescentiae. Mortality was recorded after 3 and 7 days, while progeny production was assessed after 42 days. Control samples without treatment were also included, and all experiments were conducted under the same controlled conditions. Our results indicated that zeolite was more effective than kaolin, regardless of the dose rates tested. Parental mortality reached 100% on wheat treated with 1000 ppm of zeolite after only 3 days of exposure. In contrast, survival of T. putrescentiae was noted in all doses of kaolin. Moreover, progeny production in the treated substrate was not avoided even in the highest dose of kaolin but was totally (100%) suppressed at 500 and 1000 ppm. Our results illustrate that zeolite was very effective for the control of this species, even at short exposure intervals, and hence, can be considered further as a grain protectant.